THE CONTINUAL FORMING AND CONTRIBUTION OF INFECTIVE JUVENILES PRODUCED VIA ENDOTOKIA MATRICIDA OF ENTOMOPATHOGENIC NEMATODES IN THE FAMILY OF STEINERNEMATIDAE AND HETERORHABDITIDAE - Yuliantoro Baliadi; E. Kondo; T. Yoshiga (Indonesian Journal of Agricultural Science, 2009)
The non-feeding developmentally arrested infective juveniles (IJs) of entomopathogenic nematodes in the family of Steinernematidae and Heterorhabditidae seek out a susceptible insect host and initiate infections. The aim of the research was to examine the continualforming and contribution of IJs produced via endotokia matricida (IJs-EM) of Heterorhabditis bacteriophora, Steinernema glaseri, and S. carpocapsae. The research was conducted at the Laboratory of Nematology of the Saga University, Japan (April 2001-April2002) and the Laboratory of Nematology of the Indonesian Legume and Tuber Crops Research Institute (June 2003-October 2004). The nematode progenies were investigated using the greater wax moth, Galleria mellonella, pre-inoculated with 50 IJs at 25°C.Results showed that three reproductive adult generations were observed at day 18th. There were 135,000, 128,000 and 133,000 IJs per insect cadaver produced in H. bacteriophora, S. glaseri and S. carpocapsae, respectively. Endotokia matricida contributed a higher number of IJs than that of a normal mode of IJs production. The ratios are 81%, 28% and 64% for H. bacteriophora, S. glaseri, and S. carpocapsae of the IJs total production, respectively. Among the generations, the highest contribution of IJs was come from thethird adult generation bearing endotokia matricida, i.e., 63%, 24% and 51% for the three nematode species. Although the IJs-EM were more transparent compared to the normal IJs, they were morphologically similar. The results show that endotokia matricida has a pivotal role in a species maintenance and survival strategy of entomopathogenic nematodes in extreme environmental conditions.